Cyanuric Chloride-Catalyzed Michael Addition of Indoles to Nitroolefins under Solvent-Free Conditions - Xiao Juan Yang; Yun Jing (Journal of Chemistry)
Cyanuric chloride is an inexpensive, efficient, and mild catalyst for the Michael addition of indoles to nitroolefins at 70°C under solvent-free conditions. The simple experimental procedure, solvent-free reaction conditions, utilization of an inexpensive and readily available catalyst, short period of conversion, and excellent yields are the advantages of the present method.